2020
DOI: 10.1097/sla.0000000000003845
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Comparison of Robotic and Laparoscopic Gastrectomy for Gastric Cancer

Abstract: Objective: To compare long-term outcomes between robotic and LG approaches using propensity score weighting based on a generalized boosted method to control for selection bias. Summary of Background Data: Minimally invasive surgical approaches for GC are increasing, yet limited evidence exists for long-term outcomes of robotic gastrectomy (RG). Methods: Patients (n ¼ 2084) with GC stages I-III who underwent LG or RG between 2009 and 2017 were analyzed. Generalized boosted method was used to estimate a propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
3
43
0
1
Order By: Relevance
“…La ausencia de conversión a cirugía abierta en este trabajo puede estar explicada por la exclusión de pacientes con lesiones abultadas y con gran carga ganglionar, así como la experiencia previa con el manejo abierto de éstos procedimientos y la utilización frecuente de técnicas mínimamente invasivas en otros procedimientos oncológicos digestivos [34][35][36][37][38] . El tiempo operatorio prolongado en ambos tipos de procedimientos (especialmente en los robóticos), con respecto a los procedimientos abiertos, es una de las desventajas de estas técnicas 39,40 .…”
Section: Discussionunclassified
“…La ausencia de conversión a cirugía abierta en este trabajo puede estar explicada por la exclusión de pacientes con lesiones abultadas y con gran carga ganglionar, así como la experiencia previa con el manejo abierto de éstos procedimientos y la utilización frecuente de técnicas mínimamente invasivas en otros procedimientos oncológicos digestivos [34][35][36][37][38] . El tiempo operatorio prolongado en ambos tipos de procedimientos (especialmente en los robóticos), con respecto a los procedimientos abiertos, es una de las desventajas de estas técnicas 39,40 .…”
Section: Discussionunclassified
“…Despite RCTs on long-term outcomes are still lacking, many studies [ 37 , [58] , [59] , [60] , [61] , [62] ] reported that robotic gastrectomy for AGC is oncologically adequate when compared to LG or OG. Lately, Shin [ 63 ] demonstrated in a large propensity score-weighted analysis of 2084 consecutive patients underwent RAG vs LAG, no statistical difference in 5-years overall survival and 5-years recurrence-free survival after a mean follow up of 52 months. In a recent meta-analysis, Liao [ 64 ] compared 1009 RG vs 2401 LG with no significant differences in OS, DFS, RFS and recurrence rates between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients had open surgery, and it may be that a move toward laparoscopic surgery could improve these outcomes with several recent studies suggesting comparable long term outcomes 40e42 and the potential for robotic surgery to have an equally effective oncological profile. 43 Although laparoscopic surgery has not been adopted at this center, there has been recent commencement of a robotic program. It has been felt by the surgeons involved that this may confer advantages with excellent visualization and improved surgical dexterity.…”
Section: Discussionmentioning
confidence: 99%